2010
DOI: 10.1016/j.cell.2010.07.046
|View full text |Cite
|
Sign up to set email alerts
|

A Bacterial mRNA Leader that Employs Different Mechanisms to Sense Disparate Intracellular Signals

Abstract: SUMMARY Bacterial mRNAs often contain leader sequences that respond to specific metabolites or ions by altering expression of the associated downstream protein coding sequences. Here we report that the leader RNA of the Mg2+ transporter gene mgtA of Salmonella enterica, which was previously known to function as a Mg2+-sensing riboswitch, harbors an 18-codon proline-rich open reading frame – termed mgtL – that permits intracellular proline to regulate mgtA expression. Interfering with mgtL translation by geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
115
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(128 citation statements)
references
References 47 publications
6
115
1
Order By: Relevance
“…The role of mgtL is reminiscent of the regulatory functions of short ORFs in the trp, his, and other amino acid biosynthetic operons, in which the efficiency of translation of the leader peptide regulates termination or read-through of transcription into the rest of the operon (14). However, opposing conclusions were reached in previous work for the role of Pro in the regulation of mgtA expression: Park et al (12) suggested that low levels of Pro-charged tRNA Pro increase expression of mgtA, whereas Zhao et al (13) concluded that Pro has no role in mgtA regulation. Subsequent Significance Mg 2+ is an important signal for the regulation of virulence and thermotolerance in Salmonella enterica.…”
mentioning
confidence: 55%
See 4 more Smart Citations
“…The role of mgtL is reminiscent of the regulatory functions of short ORFs in the trp, his, and other amino acid biosynthetic operons, in which the efficiency of translation of the leader peptide regulates termination or read-through of transcription into the rest of the operon (14). However, opposing conclusions were reached in previous work for the role of Pro in the regulation of mgtA expression: Park et al (12) suggested that low levels of Pro-charged tRNA Pro increase expression of mgtA, whereas Zhao et al (13) concluded that Pro has no role in mgtA regulation. Subsequent Significance Mg 2+ is an important signal for the regulation of virulence and thermotolerance in Salmonella enterica.…”
mentioning
confidence: 55%
“…Our observation that the replacement of three Pro codons nearly abolished expression of mgtA suggests that the 5′ LR mRNA favors the formation of stem loop B and enables Rho to terminate transcription. Park et al (12) and Zhao et al (13) constructed mutants in which various combinations of Pro codons in mgtL were substituted by other amino acid codons, and they also found that substitutions of Pro codons in mgtL diminished the sensitivity of the expression of mgtA to the Mg 2+ concentration.…”
Section: A Mutationmentioning
confidence: 99%
See 3 more Smart Citations